2013
DOI: 10.1111/fwb.12109
|View full text |Cite
|
Sign up to set email alerts
|

The influence of coarse‐scale environmental features on current and predicted future distributions of narrow‐range endemic crayfish populations

Abstract: Summary 1. A major limitation to effective management of narrow‐range crayfish populations is the paucity of information on the spatial distribution of crayfish species and a general understanding of the interacting environmental variables that drive current and future potential distributional patterns. 2. Maximum Entropy Species Distribution Modeling Software (MaxEnt) was used to predict the current and future potential distributions of four endemic crayfish species in the Ouachita Mountains. Current distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 87 publications
(177 reference statements)
0
19
0
Order By: Relevance
“…The importance of various local‐ and landscape‐scale variables was species‐ and spatial scale dependent. This is in accordance with a previous multiscale crayfish modelling study that found that finer grain data (1 versus 4.5 km 2 ) yielded more accurate distribution models and predictions (Dyer et al ., ). However, even their finer‐resolution data were relatively coarse compared to the local‐scale variables used in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of various local‐ and landscape‐scale variables was species‐ and spatial scale dependent. This is in accordance with a previous multiscale crayfish modelling study that found that finer grain data (1 versus 4.5 km 2 ) yielded more accurate distribution models and predictions (Dyer et al ., ). However, even their finer‐resolution data were relatively coarse compared to the local‐scale variables used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Rock fragment volume is therefore a geologic measure of the percentage of rock in the soil, and not a measure of streambed particle size. The percentage of rocky soils is important to smallmouth bass in Missouri (Brewer et al ., ), as are soils and geology to crayfish distribution in the Ozarks Highlands and Ouachita Mountains (Westhoff et al ., ; Dyer et al ., ). It is unclear in our study and previous studies if the link between soils, geology and narrow‐range endemic crayfish distribution is due to direct or indirect effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distributions are assumed to represent adaptive significance to a species and as such SDMs have been used extensively to predict distributions across terrestrial, freshwater, and marine landscapes (Elith & Leathwick, ). Understanding a species' distributions can drive conservation planning (Liang et al ., in press; Maloney et al ., ), identify areas of conservation importance (Moilanen, ), highlight factors related to species decline (e.g., Anadón et al ., ; Lötters et al ., ), and predict future distributions due to anthropogenic disturbance (Dyer et al ., ). We provide a basis for future conservation efforts for the Arkansas River shiner by quantitatively mapping the current and historic range of the species.…”
Section: Discussionmentioning
confidence: 99%
“…Aquatic ecosystems are hierarchically structured, with terrestrial landscape features constraining physicochemical processes and biotic structure at finer scales (Frissell, Liss, Warren, & Hurley, ). For example, hierarchical structuring of habitat use has been observed across a range of aquatic biota (e.g., fish, Brewer, Rabeni, Sowa, & Annis, ; Worthington, Brewer, Grabowski, & Mueller, ; crayfish, Dyer, Brewer, Worthington, & Bergey, ; and freshwater mussels, McRae, Allan, & Burch, ; Shea, Peterson, Conroy, & Wisniewski, ). The flow regime (i.e., timing, rate of change, duration, frequency, and magnitude of stream discharge) is also a product of the surrounding landscape (e.g., land use and topography) and largely dictates channel formation and ecological processes at multiple spatial and temporal scales (Poff, ).…”
Section: Introductionmentioning
confidence: 99%